The role of racial harmony in nation building / Abdul Raufu Ambali - Ambali, Abdul Raufu (Universiti Teknologi MARA, Shah Alam, 2004)
Originally, nation-building referred to the efforts of newly-independent nations, notably the nations of developing countries, to reshape colonial territories that had been carved out by colonial powers without regard to ethnic or other boundaries. These reformed states would then become viable and coherent national entities. At a deeper level, national identity needed to be deliberately constructed by molding different groups into a nation, especially since colonialism had used divide and rule tactics to maintain its domination and combine ethnic groups of different cultural background together. In terms of racial harmony, one of the most successful nation-building efforts has been in Singapore, where it has a mixture of Chinese, Tamil, Malay, Eurasian and other races. Another successful type is Malaysia, which has a mixture of Malay, Chinese, Indian and other races.